2015
DOI: 10.1007/s12035-015-9435-4
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Biomarkers of Sporadic Parkinson’s Disease and LRRK2 Kinase Inhibition

Abstract: It has been uncertain whether specific disease-relevant biomarker phenotypes can be found using sporadic Parkinson’s disease (PD) patient-derived samples, as it has been proposed that there may be a plethora of underlying causes and pathological mechanisms. Fibroblasts derived from familial PD patients harboring leucine-rich repeat kinase 2 (LRRK2), PTEN-induced putative kinase 1 (PINK1), and Parkin mutations show clear disease-relevant mitochondrial phenotypes, which are exacerbated under conditions of pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 49 publications
1
63
0
Order By: Relevance
“…The role of LRRK2 in macroautophagy has also been intensively investigated in previous studies (54), several of which concluded that its effect is proautophagic (10,17,19,(57)(58)(59), and others reporting an inhibitory effect (20,60,61) or no effect (62). Previous attempts to address the impact of LRRK2 on basal mitophagy (52,58), which is unaffected by PINK1 and Parkin (63, 64) showed opposing effects, whereas a single study assessing toxin-induced mitophagy in fibroblasts from patients with sporadic and LRRK2-linked PD, using colocalization of TOMM20 and the lysosomal marker LAMP1 as a supposed "mitophagy index" was inconclusive (65). Only one previous study investigated, in detail, the direct impact of LRRK2 on PINK1/Parkin-dependent mitophagy, and its findings are consistent with our observations (66).…”
Section: Parkin-dependent Mitophagy Is Impaired In Fibroblasts From Pmentioning
confidence: 99%
“…The role of LRRK2 in macroautophagy has also been intensively investigated in previous studies (54), several of which concluded that its effect is proautophagic (10,17,19,(57)(58)(59), and others reporting an inhibitory effect (20,60,61) or no effect (62). Previous attempts to address the impact of LRRK2 on basal mitophagy (52,58), which is unaffected by PINK1 and Parkin (63, 64) showed opposing effects, whereas a single study assessing toxin-induced mitophagy in fibroblasts from patients with sporadic and LRRK2-linked PD, using colocalization of TOMM20 and the lysosomal marker LAMP1 as a supposed "mitophagy index" was inconclusive (65). Only one previous study investigated, in detail, the direct impact of LRRK2 on PINK1/Parkin-dependent mitophagy, and its findings are consistent with our observations (66).…”
Section: Parkin-dependent Mitophagy Is Impaired In Fibroblasts From Pmentioning
confidence: 99%
“…The recruitment of Drp‐1 to mitochondrial and subsequent fission in PD patient‐derived fibroblasts and human SH‐SY5Y cells was found to be dependent upon LRRK2 kinase activity . Given the recent identification of Rab GTPases, specifically Rab7, as bonafide LRRK2 substrates, it is likely that mutant LRRK2 activity could drive mitochondrial fragmentation observed in PD patients by assembling the protein machinery and activating membrane fusion …”
Section: Parkinson's Disease Relevant Protein Kinasesmentioning
confidence: 99%
“…Fibroblasts from PD patients do exhibit more mitochondrial fragmentation and enhanced mitophagy initially compared to control cells. Thus, the role of LRRK2 in mitophagy will require a closer examination …”
Section: Parkinson's Disease Relevant Protein Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al, 2012). Accordingly, a number of different cell types, including fibroblasts and iPSC-derived neurons from PD patients harboring mutations in LRRK2 exhibit increased oxidative stress and reactive oxygen species and defects in mitochondrial network integrity (Sison et al, 2018;Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%